Nomenclatural remarks to the classifcation of plant communites along post-fire succession - Kavgaci, Ali; Šilc, Urban; Basaran, Saime; Marinšek, Aleksander; Basaran, Mehmet Ali; Košir, Petra; Balpinar, Neslihan; Arslan, Münevver; Denli, Özge; Čarni, Andraž (Hacquetia, 2018)
This paper contains the original diagnoses of new syntaxa and typifcations of existing names of syntaxa from paper “Classification of plant communities along post-fire succession in Pinus brutia stands in southern Antalya (Turkey)” that was published in Turkish Journal of Botany. As journal has only on-line version according to ICPN descriptions are not valid. We described syntaxa: Eryngio falcati-Securigerion securidacae all. nova, Ajugo chiae-Lactucetum serriolae ass. nova, Phlomido grandiﬂorae-Cistetum salvifolii ass. nova, and Arbuto andrachnes-Quercetum cocciferae ass. nova and selected nomenclatural type for Querco-Phillyreetum mediae Barbero & Quézel 1976.